2002
DOI: 10.1111/1469-7610.00006
|View full text |Cite
|
Sign up to set email alerts
|

Childhood epilepsy in relation to mental handicap and behavioural disorders

Abstract: Epidemiological studies indicate that there is a high rate of mental retardation and behavioural problems in children with epilepsy. In some cases both the epilepsy and the mental retardation will have a common cause, such as a metabolic disorder or brain trauma. However, in other children, the epilepsy itself may cause either temporary or permanent learning problems. When permanent learning disability can be prevented it is important to treat the epilepsy early and effectively. Children with specific learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 185 publications
(160 reference statements)
0
36
2
1
Order By: Relevance
“…This is in agreement with Svoboda, who reported that difficulties with auditory discrimination in a noisy background were seen in 24%, and difficulties with short-term memory in 61% of children referred to the Kansas City Epilepsy Center, 5 and such difficulties have also been reported by others. 4,23 However, our results in different subtests of auditory attention and narratives were contradictory and could reflect different demands in these subtests or fluctuating ability.…”
Section: Discussioncontrasting
confidence: 58%
“…This is in agreement with Svoboda, who reported that difficulties with auditory discrimination in a noisy background were seen in 24%, and difficulties with short-term memory in 61% of children referred to the Kansas City Epilepsy Center, 5 and such difficulties have also been reported by others. 4,23 However, our results in different subtests of auditory attention and narratives were contradictory and could reflect different demands in these subtests or fluctuating ability.…”
Section: Discussioncontrasting
confidence: 58%
“…In a thorough review of children with behavioural problems, MR and epilepsy, Besag summarised that many children with epilepsy have global or specific learning difficulties, and that generally, the greater the degree of pre-existing MR, the higher the risk of developing epilepsy (Besag, 2002). Besag questions whether lower intellectual functioning in epilepsy reflects a pre-existing genetically determined deficit or a consequence of having epilepsy.…”
Section: Factors For Co-morbiditymentioning
confidence: 99%
“…Notably though, the younger twin was treated with AED intervention. This is important as Besag (2002) states that a learning disability [LD] must be distinguished from MR, as MR is a permanent learning disability, while a state-dependant LD is potentially reversible. Besag defines state-dependant LD as "a learning disability that is caused by factors currently affecting the individual that are potentially reversible or treatable" and severe LD with autistic symptomology can be profoundly reversed by appropriate treatment strategies such as AEDs (ibid., p.110).…”
Section: Factors For Co-morbiditymentioning
confidence: 99%
“…It is characterised by hypsarrythmia, learning problems and infantile spasms, with psychiatric disorders manifesting in up to a third. Autistic regression has been observed amongst those with behavioural disorder, and more than half of those with West syndrome associated with TS have reportedly remained autistic [30].…”
Section: Epilepsy In Asdmentioning
confidence: 99%